Improvement of traditional gold recovery process for jewellery scrap / Saadiah Kaspin - Kaspin, Saadiah (2008)
Problem Statement: The problem statement in this research is " to refining and recovering the gold scrap from the work bench". Current application in jewelry fabrication process includes technique like filing, piercing, grinding, drilling and etc are amongst the popular application that is widely used for a long time. All this while, the process has yielded various type of scrap. These scrap (in dust form) would eventually mix up with other form of dust from polishing wheel vacuum collectors and sweeping floor dust and it's very difficult to recognize. Gold and other precious metals "lost" during the fabrication process can be a significant cost factor that impacts product cost and business competitiveness. Much of the scrap generated in production can be cleaned and recycled, but contaminated scrap and other wastes need to be collected and refined back to pure gold to recover the value of the precious metal. Such scraps and wastes need to be pre-treated before refining to reduce costs and maximize recovery of precious metals.